Development of Innovation Activity in The Agricultural Sector - Tatiana Vitalievna POGODINA; Tatiana Gennadievna POPADYUK; Lyudmila Mikhailovna KORNILOVA; Evgeny Alekseyevich IVANOV; Andrey Evgenievich MAKUSHEV (Communications of International Proceedings, 2021)
A modern stage of agricultural sector performance corresponds to the transfer to innovation-driven growth model, focused on the increase of production performance based on design and engineering modernization of material and technical foundation and on organizational and managerial upgrade. The purpose of the paper is to offer modern approaches to the increase of innovation activity of agricultural manufacturer based on the trend analysis for agricultural production. The dynamic, statistical, comparative and coefficient study methods are used in this work. The study results are shown in the following key statements. A conclusion is made that instable parameters of the dynamics of the agricultural production are caused by low innovative activity of agricultural manufacturers. The presence of innovation multiplier is explained and calculated for separate agricultural activities, which had the highest values in animal breeding and in support activities in the agricultural crops and post-harvest treatment. A necessity to implement cluster approach into agricultural and agro-industrial production is proved. To detect regions, for which it is reasonable to form and develop agricultural clusters, it is suggested to use location quotient for agricultural production. The examples of establishing agricultural and agro-industrial clusters in the Belgorod and Bryansk regions and the possibility to use the progressive experience in other subjects of Russia are studied. Conclusions and suggestions are made to increase the innovative activity of the territorial agricultural manufacturers.